Problems and Prospects of Cross-Border Cooperation in Ukraine - V. PARKHOMENKO (National Academy of Statistics, Accounting and Audit, 2021)
The purpose of the article is to analyze the current state of cross-border cooperation in Ukraine, characterize the main problems and outline the prospects for its development.